Attribute Preference Hierarchy Based Segments in the Indian Car Tyre Replacement Market – An Exploratory Study - Sharma, Anshu (Indian Journal of Marketing, 2020)
Purpose: This study was undertaken during February-June 2019 to understand the attributes car owners considered while making a tyre purchase decision, and to understand if any meaningful customer segments emerged on the basis of their attribute preference hierarchy. Review of literature did not find much of note on this topic. This paper filled this void in research. This paper provided usable insights for the $ 8.5 billion Indian tyre industry. Approach: Exploratory personal interviews of car owners were conducted in the city of Bangalore to arrive at a consideration set of seven unique attributes. These attributes were then tested for their relative importance by conducting a mix of personal and online surveys on a pan India level. A total of 112 responses were analyzed to arrive at the top five attributes. As a next step, the κ-means clustering technique was applied to the 112 responses to arrive at meaningful customer segments. Findings: The top five attributes which emerged as critical to the tyre purchase decision were – quality, price, brand, safety, and reliability. Four unique segments emerged with unique attribute preferences. The first segment considered quality and price as the top attributes and no significant importance was attached to the other attributes. The second segment only looked at brand and quality while deciding on the purchase. The third segment looked at safety along with brand and price as the top decision attributes. The fourth segment was very peculiar as it assigned equal importance to all five attributes.